Implementation of Corporate Social Responsibility at Grand Hotel Bayu Hill in The Review of The Grant Agreement - Silvia, Radha; Mubarak, Husni; Reza, T. Surya (Sharia Faculty Islamic Economic Law Study Department, 2024)
This article aims to analyze the practice or implementation of Corporate Social Responsibility at the Grand Bayu Hill Hotel in Bebesen District, Central Aceh Regency. To obtain data, the author used a qualitative method, where the main source was obtained from interviews and observations between the author and the company (stakeholders). Meanwhile, secondary data was obtained from reading sources such as books, journals and other sources related to this research topic. The research results show that; first, regarding the forms of distribution of funds for the Implementation of Corporate Social Responsibility at the Grand Hotel Bayu Hill. Second, regarding supervision of the implementation of Corporate Social Responsibility at the Grand Hotel Bayu Hill, it has not been fully maximized, in fact there is no supervision from the central or regional government regarding CSR, whereas social and environmental responsibility (TJSL) has been regulated based on article 74 paragraph (4) of Law 40 /2007 is imperative, that is, it is only regulated by Government Regulation, in other words, CSR is under the auspices of the government. Third, in reviewing the grant contract, according to Islamic law and the opinion of the Ulama, CSR implementation practices at the Grand Hotel Bayu Hill are still not optimal when viewed from the terms and conditions of the grant. The defect lies in the gift giver and the shigat (promise of qabul) when giving goods/money to be gifted to the recipient of the gift.